A National Wealth Approach to Banking Crises and Financial Stability - Frecaut, Olivier (IMF Working Papers; Working Paper ;, 2016)
The paper explores a different, supplementary way to assess and manage a particular type of banking crises, those arising from a rise of nonperforming loans to the corporate sector. It relies on a 'national wealth approach,' focusing on the distribution of net wealth among economic sectors and its interaction with developments in the banking system. It identifies avenues for policy response optimization, based on an integrated macrofinancial analytical framework, both for the prevention and the resolution of these types of economic events.